The Effect of Product Availability and Pricing on Customer Loyalty mediated by Purchase Decision - Aulia, Elcyntha; Suci, Rahayu Puji; Intyas, Yekti; Iswari, Hanif Rani (Clean and Sustainable Production, 2024)
The approach in this research is in the form of quantitative descriptive research. This research uses primary and secondary data. The sample consisted of 45 egg resellers at UD. Sari Laut Blitar City using nonprobability sampling techniques. The research results show that: (1) Good product availability cannot increase customer loyalty (2) Good pricing cannot increase customer loyalty, (3) Good product availability can increase purchasing decisions (4) Good pricing can increase purchasing decisions, (5) Purchasing decisions made by egg resellers at UD. Sari Laut can increase customer Loyalty, (6) Purchasing decisions do not have a mediator role in the relationship between product availability and customer loyalty, (7) Increased purchasing decisions act as a mediator in the influence of pricing on customer loyalty.